2004
DOI: 10.1021/jm049625o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Electrochemistry, and Bioactivity of the Cyanobacterial Calothrixins and Related Quinones

Abstract: The calothrixins are quinone-based natural products isolated from Calothrix cyanobacteria which show potent antiproliferative properties against several cancer cell lines. Preliminary mechanistic studies suggest that the biological mode of action of the calothrixins may be linked to their ability to undergo redox cycling. In this study we compare the bioactivities of the calothrixins with those of structurally related quinones in order to identify the structural features in the calothrixins essential for biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…Ellipticine quinone (22) was reported to have an EC 50 value of 0.15 lM against the HeLa cell lines. 10 The observed EC 50 value for isoquinolinedione (12) is 80-fold less than this, supporting the importance of rings A-C in the biological activity against HeLa cell lines. Similarly, the absence of the nitrogen atom in the D-ring (indolophenanthrene 7 versus Calothrixin 6) resulted in a drop in the potency observed.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Ellipticine quinone (22) was reported to have an EC 50 value of 0.15 lM against the HeLa cell lines. 10 The observed EC 50 value for isoquinolinedione (12) is 80-fold less than this, supporting the importance of rings A-C in the biological activity against HeLa cell lines. Similarly, the absence of the nitrogen atom in the D-ring (indolophenanthrene 7 versus Calothrixin 6) resulted in a drop in the potency observed.…”
mentioning
confidence: 83%
“…(12) 12 ± 1 9 ± 2 >50 a In a previous study with HeLa cells, the EC 50 for benzocarbazoledione was found to be 0.43 ± 0.1 lM. 10 the different cell lines also highlight its specific utility against HeLa cells. With respect to P388 cells, only murrayaquinone A shows desirable selectivity.…”
Section: -Methylcarbazoledionementioning
confidence: 94%
See 2 more Smart Citations
“…The pentacyclic carbazole alkaloids calothrixin A (1) and B (2) were isolated by Rickards et al from Calothrix cyanobacteria in 1999. 1 Calothrixins possess an unprecedented indolo[3,2-j]-phenanthridine framework with a striking assemblage of quinoline, quinone and indole pharmacophores.…”
Section: Introductionmentioning
confidence: 99%